2023
DOI: 10.1039/d2bm01581a
|View full text |Cite
|
Sign up to set email alerts
|

Lipid nanoparticle-based mRNA candidates elicit potent T cell responses

Abstract: Addition of limited amounts of fusogenic lipid DOPE (Orange) and beta-sitosterol (red) improves transfection efficacy of dendritic cells and improves CDB* T-cell responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…54 Another study explored the role of the sterol component (cholesterol versus βsitosterol) as well as the fusogenic helper lipid in optimizing the transfection efficiency and T cell activation by mRNA LNPs. 55 The search for the optimal lipids for mRNA LNPs has been the subject of many investigations. Researchers recently synthesized more than 100 lipids to optimize mRNA stability and delivery and found that lipids with branched hydrophobic tails outperformed linear lipids.…”
Section: Platformsmentioning
confidence: 99%
See 1 more Smart Citation
“…54 Another study explored the role of the sterol component (cholesterol versus βsitosterol) as well as the fusogenic helper lipid in optimizing the transfection efficiency and T cell activation by mRNA LNPs. 55 The search for the optimal lipids for mRNA LNPs has been the subject of many investigations. Researchers recently synthesized more than 100 lipids to optimize mRNA stability and delivery and found that lipids with branched hydrophobic tails outperformed linear lipids.…”
Section: Platformsmentioning
confidence: 99%
“…An mRNA LNP formulation was designed to target APCs in the spleen by optimizing the lipid composition, specifically the type of helper lipid . Another study explored the role of the sterol component (cholesterol versus β-sitosterol) as well as the fusogenic helper lipid in optimizing the transfection efficiency and T cell activation by mRNA LNPs …”
Section: Lipid-based Nps As Cancer Vaccine Platformsmentioning
confidence: 99%
“…There are several biomaterial designs and modifications that show promise for the safe delivery of mRNA, including lipids, lipid-like materials, polymers, and inorganic nanoparticles . Currently, lipid nanoparticles (LNPs) are the state-of-the-art vector for packaging, protecting, and releasing mRNA molecules within cells, as evidenced by the success of two COVID-19 mRNA-LNP vaccine formulations that received FDA approval in 2020. LNPs are typically composed of four lipid componentsan ionizable lipid, cholesterol, a helper lipid, and a poly­(ethylene glycol)-lipid conjugate, which can be varied to produce distinct formulations with desired physicochemical properties. However, the efficacy of LNPs in transfecting cells is limited by their ability to induce endo/lysosomal escape since they enter cells through endocytosis and are subjected to endolysosomal trafficking . Typically, less than 5% of the intracellularly delivered dose of mRNA by LNPs is able to reach the cytoplasm .…”
Section: Introductionmentioning
confidence: 99%
“…2 Currently, the most advanced nonviral nucleic acid delivery system is lipid nanoparticles (LNPs). [14][15][16] LNPs are composed of an ionizable lipid to condense the genetic cargo and release it after entering the cells; a cholesterol moiety to stabilize the LNP structure; a helper lipid; and a PEGylated lipid to improve colloidal stability and reduce protein absorption. 17 The first siRNA drug, named Onpattro (Patisiran), was approved in 2018 by the FDA and was designed to treat polyneuropathies induced by hereditary transthyretin-mediated amyloidosis (hATTR) in adults.…”
Section: Introductionmentioning
confidence: 99%